DEAD-Box Helicase 27 Triggers Epithelial to Mesenchymal Transition by Regulating Alternative Splicing of Lipoma-Preferred Partner in Gastric Cancer Metastasis - Jin, Yirong; Yang, Suzhen; Gao, Xiaoliang; Chen, Di; Luo, Tingting; Su, Song; Shi, Yanting; Yang, Gang; Dong, Lei; Liang, Jie (Frontiers in Genetics, 2022)
DEAD-box helicase 27 (DDX27) was previously identified as an important mediator during carcinogenesis while its role in gastric cancer (GC) is not yet fully elucidated. Here, we aim to investigate the mechanism and clinical significance of DDX27 in GC. Public datasets were analyzed to determine DDX27 expression profiling. The qRT-PCR, western blot and immunohistochemistry were employed to investigate DDX27 expression in GC cell lines and clinical samples. The role of DDX27 in GC metastasis was explored in vitro and in vivo. Mass spectrometry, RNA-seq and alternative splicing analysis were conducted to demonstrate DDX27-mediated molecular mechanisms in GC. We discovered that DDX27 was highly expressed in GCs, and high level of DDX27 indicated poor prognosis. Increased DDX27 expression could promote GC metastasis while DDX27 knockdown impaired GC aggressiveness. Mechanically, LLP expression was significantly altered after knocking down DDX27, and further results indicating that LPP may be regulated by DDX27 via alternative splicing. In summary, our study indicated that DDX27 contributed to GC malignant progression via a pro-metastatic DDX27/LPP/EMT regulatory axis.